2009
DOI: 10.1080/00016340903147397
|View full text |Cite
|
Sign up to set email alerts
|

Association between experiencing rape, police reporting, and self‐reported health among women visiting three gynecology clinics in Sweden

Abstract: Objective. To describe the frequency of police reporting among rape victims based on two hypotheses: (1) victims of rape more often report poor health than those who have not been victims of any abuse, and (2) victims who report abuse to the police are more likely to state poor self-reported health than those who do not report any abuse. Design. Cross-sectional questionnaire study. Setting. Three Swedish departments of obstetrics and gynecology. Sample. From an original sample of 2,439 women, those who had exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The overall low disclosure rate highlights the need for increased awareness of SV and available response services. Community norms have been shown to play a role in responses to disclosure and children’s willingness to disclose SV; research should further examine Kenyan attitudes towards SV (Davidsson et al, 2009). This study may inform the Government of Kenya’s efforts to strengthen the health, justice, and education infrastructures to respond to SV against children and to raise awareness about the availability and confidential nature of these services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall low disclosure rate highlights the need for increased awareness of SV and available response services. Community norms have been shown to play a role in responses to disclosure and children’s willingness to disclose SV; research should further examine Kenyan attitudes towards SV (Davidsson et al, 2009). This study may inform the Government of Kenya’s efforts to strengthen the health, justice, and education infrastructures to respond to SV against children and to raise awareness about the availability and confidential nature of these services.…”
Section: Discussionmentioning
confidence: 99%
“…Children who experience SV perpetrated by a stranger are more likely to disclose SV in higher-income countries (Priebe & Svedin, 2008; Smith et al, 2000). This finding may be due to community perceptions that strangers usually perpetrate SV, implying that it may not translate to settings with different perceptions of SV (Davidsson, Benjaminsson, Wijma, & Swahnberg, 2009). Additionally, children may more clearly understand that the act is inappropriate when the perpetrator is unfamiliar to them (Smith et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These findings corroborate those of prior studies undertaken in Sweden, in which the same instrument for determining women's exposure to violence was used. Davidsson, Benjaminsson, Wijma, and Swahnberg (2009) demonstrated that women in Sweden who had been raped had more often poor selfreported health, and among those who had in addition been exposed to physical and mental violence, the association was even stronger. This finding is similar to the results of the present study: among women who have been exposed to all three forms of violence, the association with poor self-perceived health and limited daily activities was the strongest.…”
Section: Discussionmentioning
confidence: 99%
“…We have from time to time addressed the topic of violence to women and rape in AOGS articles (4–6). Cecilie Hagemann and colleagues in Trondheim and Oslo, Norway, write on this topic on pp.…”
mentioning
confidence: 99%
“…The two pictures of a patient (published with her consent) say much about the topic, so having seen these you might be interested to return to the text! We have from time to time addressed the topic of violence to women and rape in AOGS articles (4)(5)(6). Cecilie Hagemann and colleagues in Trondheim and Oslo, Norway, write on this topic on pp.…”
mentioning
confidence: 99%